Sexist language in the speech of Moslem female preachers (critical discourse analysis) - Rahmah, Risha Iffatur; Yohanes, Budinuryanta; Suhartono, Suhartono (citeus, 2020)
This study aims to find sexist language in the speech of female preachers through representation, interpretation, and forms of discrimination in the text. This study used a qualitative phenomenological research method and used critical discourse analysis by Faircloughn as supporting the data. The data shows that females speak more sexist if they talk to the same gender than a different gender. From this phenomenon, the impact on the use of vocabularies that license gender identity by using the terms marked, unmarked, and semantic derogation. There are other relationships with grammar using declarative, imperative, and interrogative sentence types in intentionality modalities; epistemic; deontic; dynamic. This relationship also discussed the uses of mentioning text in a text structures by convection of relationships, structuring, and ordering a text.